ANALISIS KUALITAS SOAL UAS MATA PELAJARAN IPA DI SMP ISLAM KHAIRA UMMAH KOTA PADANG KELAS VIII TAHUN AJARAN 2019/2020 - Utari Akhir Gusti (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2021)
Teachers often use educational instruments because it is more effective to see student learning outcomes. But on the other hand, many of the educational instruments are not following established standards, such as the end of the semester exams. Therefore, it is necessary to test the analysis of the end-of-semester exam questions in the Islamic junior high school (SMP Islam) of Padang because there has never been an analysis of the quality of the questions. This study was conducted to see the quality of the final semester exams in class VIII natural science subjects at SMP Islam Khaira Ummah in Padang. The tests carried out are reliability, validity, distinguishing features, and the level of difficulty of the questions. The results showed that the final semester exam questions on science class VIII with 40 items from 37 results of students with anates test. Having the reliability of the questions classified as quite reliable is 0.51. Distinguishing power with good categories is 17.5%, enough categories are 22.5%, and bad categories are 60%. The difficulty level is three very easy questions; 19 questions are medium, 11 questions, and seven are very difficult. The empirical validity of invalid questions was 67.5% or 27 items, and valid questions were 32.5% or 13 items.Keywords: Problem Analysis, Natural Science, SMP Islam Khaira Ummah